Safety Assessment of Driver Assistance Systems - Carsten, O.M.J; Nilsson, L. (European Journal of Transport and Infrastructure Research, 2001)
This paper reviews issues in and procedures for the safety evaluation of in-vehicle Advanced Driver Assistance Systems. Contrasts are drawn between the two main areas of driver assistance systems — on the one hand information systems which interact with the driver and on the other hand intervening systems which interact directly with the vehicle. Navigation systems are typical of the former category and adaptive cruise control of the latter. It is argued that, for information systems it is possible to develop a “generic” safety assessment procedure, with a single generic test. A contrast is drawn with In the area of intervening systems (driver warning and vehicle control systems), where no such generic evaluation by means of a single test is possible. Such systems differ widely in their purpose, in their intended operating environment, in their functionality and in their operating envelope. The authors propose a structured procedural approach for the safety assessment of intervening systems.